The Effects of Personal Agency on Regret. (4th July 2012) - Contractor, Sunil H.; Kumar, Piyush
ABSTRACT In this paper, we examine the role of personal agency as a key antecedent of regret that individuals experience when the outcome of their decision is unfavorable. In contrast to previous research that documents its exacerbating role, we find that personal agency mitigates regret under certain circumstances. A series of experimental studies show that personal responsibility for the decision may attenuate subjective perceptions of the extent of failure and mitigate regret. However, when the superior outcome of the foregone option is known and the failure of the chosen option is irreversible, personal agency may amplify regret. We also find that subjective failure perceptions mediate the relationship between personal agency and regret levels. Copyright © 2012 John Wiley & Sons, Ltd.